(untitled) (The Review of Diabetic Studies, 2025)
Childhood diabetes, particularly Type 1 Diabetes Mellitus (T1DM), poses significant challenges to the physical, cognitive, and psychosocial development of affected individuals. This meta-analysis synthesizes findings from peer-reviewed studies published between 2010 and 2025 to evaluate the impact of childhood diabetes on growth parameters, neurodevelopmental outcomes, and quality of life (QoL). A systematic search of Scopus, PubMed, Web of Science, and Embase databases yielded 42 eligible studies, including 18 meta-analyses and 24 longitudinal cohort studies.The results indicate that children with T1DM exhibit impaired linear growth, delayed pubertal onset, and altered body mass index trajectories, particularly in cases of poor glycemic control. Neurodevelopmental assessments reveal small-to-moderate deficits in executive functioning, attention, and memory, with early-onset diabetes (<5 years) associated with greater cognitive impairment due to recurrent hypoglycemia and glycemic variability. Psychosocial evaluations demonstrate significantly reduced QoL scores across physical, emotional, and school domains, with contributing factors including disease burden, social stigma, and family stress. The analysis highlights the importance of early diagnosis, tight glycemic control, and multidisciplinary care involving endocrinologists, psychologists, and nutritionists. Technological interventions such as continuous glucose monitoring (CGM) and insulin pump therapy show promise in improving both metabolic outcomes and QoL. However, disparities in access to care and underrepresentation of low- and middle-income populations remain critical limitations.This review underscores the need for routine developmental screening and psychosocial support in pediatric diabetes management. Future research should prioritize longitudinal studies, culturally sensitive interventions, and integration of QoL metrics into clinical practice. Addressing these challenges holistically is essential to improving long-term outcomes and ensuring optimal growth and development in children living with diabetes.